2007
DOI: 10.1002/ange.200702513
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Enantioselectivity of P‐Chiral Phosphine Ligands with Alkynyl Groups

Abstract: General.All solvents used in reactions were dried and purified according to standard procedure. NMR spectra were measured with JEOL JMN-GXS-500 (500 MHz) or JEOR JMN-LA-400 (400 MHz) spectrometer in CDCl 3 . Chemical shifts were reported in δ ppm. Optical rotationswere measured with JASCO DIP-370 polarimeter. Enantiomeric excesses were determined by HPLC analysis using Chiralcel AD, OJ-H, OD-H, OB, IA columns and varying concentrations of 2-propanol/hexane as the mobile phase. X-ray crystal structure data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Several research groups reported the efficient asymmetric synthesis of P‐stereogenic phosphorus compounds12 by resolution13 (including dynamic resolution13ac), desymmetrization,14 and catalytic asymmetric reactions 15. Recently, Imamoto et al demonstrated that P‐stereogenic phosphine ligands bearing alkynyl groups induced excellent enantioselectivity in various transition‐metal‐catalyzed asymmetric reactions 16. We anticipated that if selective mono [2+2+2] cycloaddition of symmetrical dialkynylphosphine oxides with 1,6‐diynes proceeds by using cationic rhodium(I) complexes with modified 2,2’‐bis(diphenylphosphanyl)‐1,1’‐binaphthyl (binap) ligands as a catalyst, then P‐stereogenic alkynylphosphine oxides could be accessed by desymmetrization (Scheme ) 17…”
Section: Methodsmentioning
confidence: 99%
“…Several research groups reported the efficient asymmetric synthesis of P‐stereogenic phosphorus compounds12 by resolution13 (including dynamic resolution13ac), desymmetrization,14 and catalytic asymmetric reactions 15. Recently, Imamoto et al demonstrated that P‐stereogenic phosphine ligands bearing alkynyl groups induced excellent enantioselectivity in various transition‐metal‐catalyzed asymmetric reactions 16. We anticipated that if selective mono [2+2+2] cycloaddition of symmetrical dialkynylphosphine oxides with 1,6‐diynes proceeds by using cationic rhodium(I) complexes with modified 2,2’‐bis(diphenylphosphanyl)‐1,1’‐binaphthyl (binap) ligands as a catalyst, then P‐stereogenic alkynylphosphine oxides could be accessed by desymmetrization (Scheme ) 17…”
Section: Methodsmentioning
confidence: 99%
“…The single example relating the synthesis of a set of enantiopure P-stereogenic alkynylphosphines was described by Imamoto [ 5 ] ( Scheme 8 ). The procedure relies on the in situ generation of a P-stereogenic bromophosphine-borane from an enantiopure secondary phosphine-borane via deprotonation by n -butyllithium in diethyl ether at −78 °C and subsequent halogenation of the resulting lithium phosphido-borane by treatment with dibromoethane.…”
Section: Nucleophilic Substitution At P-atom Of Halophosphinesmentioning
confidence: 99%
“…The Imamoto group [ 5 ] described a 4-step reaction sequence allowing the synthesis of an alkynyl variant of BisP* ligands, analogous to DIPAMP [ 27 ], from an enantiopure silyl alkynylphosphine-borane ( Scheme 18 ). The first step was a dimerization reaction through copper(II)-catalyzed oxidative coupling leading to the bis-alkynylphosphine-borane 2 .…”
Section: Transformation Of Alkynylphosphorus Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to rhodium catalysts, other transition metal catalysts may be used for asymmetric ring-opening reactions of oxabicyclic alkenes. These include complexes of copper [ 20 25 ], palladium [ 14 15 26 31 ], iron [ 32 ], and nickel [ 33 36 ]. Recently, we reported for the first time iridium-catalyzed asymmetric ring-opening of N -Boc-azabenzonorbornadiene with a wide range of secondary amines [ 37 ].…”
Section: Introductionmentioning
confidence: 99%